Turkmenistan's Dilemma. (3rd July 2021) - Shlapentokh, Dmitry V.
ABSTRACT: Gas exports have emerged as the major source for hard currency. The income from gas exports made it possible to maintain the Russian state and economy. It is crucial for the stability of the regime. While trying to diversify the markets, the Kremlin has few choices. It could send gas either to China or Europe. Despite the existence of the Chinese market, the European market has continued to be extremely important. The Kremlin tried to minimise the completion and this explains its policy toward Turkmenistan with its rich gas deposits. Consequently, Moscow's policy in the Middle East is often conditioned by the attempt to prevent Turkmenistan from sending gas to European markets or creating any other problems for Gazprom.